Biomechanical Comparison of Vertical Mattress and Cross-stitch Suture Techniques and Single- and Double-Row Configurations for the Treatment of Bucket-Handle Medial Meniscal Tears. Issue 5 (April 2019) - Nakama, Gilberto Y.; Kaleka, Camilla C.; Franciozi, Carlos E.; Astur, Diego C.; Debieux, Pedro; Krob, Joseph J.; Aman, Zachary S.; Kemler, Bryson R.; Storaci, Hunter W.; Dornan, Grant J.; Cohen, Moises; LaPrade, Robert F.
Background: Given the variety of suturing techniques for bucket-handle meniscal repair, it is important to assess which suturing technique best restores native biomechanics. Purpose/Hypothesis: To biomechanically compare vertical mattress and cross-stitch suture techniques, in single- and double-row configurations, in their ability to restore native knee kinematics in a bucket-handle medial meniscal tear model. The hypothesis was that there would be no difference between the vertical mattress and cross-stitch double-row suture techniques but that the double-row technique would provide significantly improved biomechanical parameters versus the single-row technique. Study Design: Controlled laboratory study. Methods: Ten matched pairs of human cadaver knees were randomly assigned to the vertical mattress (n = 10) or cross-stitch (n = 10) repair group. Each knee underwent 4 consecutive testing conditions: (1) intact, (2) displaced bucket-handle tear, (3) single-row suture configuration on the femoral meniscus surface, and (4) double-row suture configuration (repair of femoral and tibial meniscus surfaces). Knees were loaded with a 1000-N axial compressive force at 0°, 30°, 60°, 90°, and 120° of flexion for each condition. Resultant medial compartment contact area, average contact pressure, and peak contact pressure data were recorded. Results: Intact state contact area was not restored at 0° ( P = .027) for the vertical double-row configuration and at 0° ( P = .032), 60° ( P < .001), and 90° ( P = .007) of flexion for the cross-stitch double-row configuration. No significant differences were found in the average contact pressure and peak contact pressure between the intact state and the vertical mattress and cross-stitch repairs with single- and double-row configurations at any flexion angles. When the vertical and cross-stich repairs were compared across all flexion angles, no significant differences were observed in single-row configurations, but in double-row configurations, cross-stitch repair resulted in a significantly decreased contact area, average contact pressure, and peak contact pressure (all P < .001). Conclusion: Single- and double-row configurations of the vertical mattress and cross-stitch inside-out meniscal repair techniques restored native tibiofemoral pressure after a medial meniscal bucket-handle tear at all assessed knee flexion angles. Despite decreased contact area with a double-row configuration, mainly related to the cross-stitch repair, in comparison with the intact state, the cross-stitch double-row repair led to decreased pressure as compared with the vertical double-row repair. These findings are applicable only at the time of the surgery, as the biological effects of healing were not considered. Clinical Relevance: Medial meniscal bucket-handle tears may be repaired with the single- or double-row configuration of vertical mattress or cross-stitch sutures.